Postoperative pain and opioid requirements in cannabis users: A new preoperative variable to consider: Dolor y requerimiento de opioides postoperatorios en pacientes consumidores de cannabis: Una nueva variable prequirúrgica a considerar - Salazar-Jaramillo , Camila (2025)
The increasingly prevalent use of cannabis appears to be one of those factors that can make the difference between a patient with adequately controlled pain and one experiencing unnecessary suffering. Therefore, we believe that recent cannabis use should be explicitly included as an item in the preoperative assessment, on the same level as tobacco or alcohol consumption.